Accelerated aqueous extraction and phytochemicals screening of eurycoma longifolia (Tongkat Ali) extract - Mohd. Amin, Nor Amaiza (2015)
The development of a rapid, robust and reliable method for extraction of plant materials is important for the screening of a wide range of plant bioactives and the discovery of biomarker. Accelerated aqueous extraction or commercially known as Accelerated Solvent Extraction (ASE) is an automated extraction technique operated at elevated temperatures and pressures to achieve extraction in a short period of time. The high temperature weakens the solute-matrix interactions and leads to a faster diffusion rate, better analyte solubility and lower solvent viscosity. This research was undertaken to evaluate the performance of an accelerated aqueous extraction of eurycomanone and other bioactive compounds from Tongkat Ali. Investigation was carried out to elucidate the effect of static cycle, static time and temperature on the content and degradation of eurycomanone. To date, there is no study being carried out on optimization of the extraction of eurycomanone from Tongkat Ali roots using this technique. The optimum operating conditions were subsequently used for the extraction of other phytochemicals. Response surface methodology was used to determine the significant operating conditions. The Box-Behnken design was implemented to maximize the response (eurycomanone content) from the resulted response surface. The extraction yield of eurycomanone are mainly affected by temperature (>100 oC) followed by the static time. A higher static time (>11 min) was found to cause eurycomanone degradation, while a lower temperature and static time reduced the extraction efficiency. The optimum conditions yielded a corresponding eurycomanone content of 9.21mg/g at static time of 8 minutes, static cycle of 5 and temperature of 90 oC. A liquid chromatography coupled with a triple quadrapole and time-of-flight, mass spectrometer (LC-QTOF-MS/MS) was used to profile the small metabolites. The major quassinoid identified were 13a(21)-epoxyeurycomanone, eurycomanone, longilactone14, 15ß-dihydroxyklaineanone, 6a-hydroxyeurycomalactone, eurycomalide B, laurycolactone A and laurycolactone B. In summary, the combination method of ASE and statistical analysis presented is an expedient technique for the phytochemicals screening of Tongkat Ali roots.